ABOUT THE THEORY OF DEXTERITY IN PHYSICAL EDUCATION - Arabjonov Shokirjon Shavkatovich (Galaxy International Interdisciplinary Research Journal, 2023)
The following article provides information about the theory of dexterity in physical education, its advantages and disadvantages. Ideas about its useful aspects have been put forward.